Featherstream - Sutherland, Ian (Department of English Language and Literature, 2016)
Featherstream is a romantic suspense novel set at the southernmost tip of Africa during the Second World War. Returning to her father's farm at Cape Agulhas for the university holidays, Anna van der Vliet stumbles on a clandestine operation to provision enemy U-boats. Her dilemma of whether to betray family or country is further complicated when she falls in love with German naval commander Thomas von Eisenheim. Anna goes on to uncover a plot by Nazi Germany and the right-wing Ossewabrandwag organisation to blow up the Union's parliament buildings and install a pro-German Afrikaner government. The novel's landscape ranges from the remote fynbos plains of Agulhas in the Southern Cape, through the Moravian hamlet of Elim to Cape Town. Based on extensive historical research, it explores the deep ideological tensions in South Africa between supporters of the pro-war government of General Jan Smuts and Doctor Daniel Malan's Purified National Party, which were mirrored in communities and families across South Africa. The driving force of the story is a young woman's struggle to reconcile divided loyalties and emerge from the emotional stranglehold of her overbearing father.